Evaluasi dan Perbaikan Antarmuka Guna Meningkatkan User Experience menggunakan Metode Usability Testing dan User Experience Questionnaire (UEQ) (Studi Kasus: Aplikasi Malang Menyapa) - Rizki Hasna Salsabil Rakha; Satrio Hadi Wijoyo; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Malang Menyapa application is an application developed by the Ministry of Sports, Culture and Tourism Office in Malang City. In its use, several usability issues were found, related to the overcrowded interface, confusing button layouts, and information that was not updated regularly. This study aims to evaluate and improve the interface in order to improve user experience using the Usability Testing and User Experience Questionnaire (UEQ). The initial evaluation results obtained are used to design a new interface in the form of a prototype. From the test results, it was found that there was an increase of 26% in the Learnability aspect, 64.85% in the Efficiency aspect, and 59.37 SUS scores on the Satisfaction aspect. In the Memorability aspect, the processing time decreased by 27.74% and the number of clicks by 2.76%. In the Error aspect, a decrease of 59% was obtained. In the results of the UEQ questionnaire testing, it was found that there was an increase in all the scales tested. The Attractiveness scale has increased by 3.45 points. The Perspicuity scale has increased by 3.58 points. The Efficiency Scale has increased by 3.34 points. The Dependability Scale has increased by 2.73 points. The Stimulation scale has increased by 2.31 points. The Novelty scale has increased by 3.14 points. Based on the comparison results, the design of the improvement solution succeeded in improving the user experience of the Malang Menyapa application.